Blisters on their feet : tales of internally displaced persons in India's North East - Das, Samir Kumar (New Delhi, India ; Thousand Oaks, Calif. : SAGE Publications, 2008)
Proceedings of four workshops organized by the Indian Council of Social Science Research-North Eastern Regional Centre.
Includes bibliographical references and index.
Keywords: INTERNALLY DISPLACED PERSONS -- INDIA, NORTHEASTERN -- SOCIAL CONDITIONS; INTERNALLY DISPLACED PERSONS -- GOVERNMENT POLICY -- INDIA, NORTHEASTERN; SOCIAL CONFLICT -- INDIA, NORTHEASTERN; ECONOMIC DEVELOPMENT -- INDIA, NORTHEASTERN